Pengaruh Penggunaan Media Video Tutorial Standar Operational Procedur (Sop) Dalam Link Quick Response Code (QR Code) Terhadap Kemampuan Mahasiswa Keperawatan Mengoperasikan Alat Syringe Pump - Dona, Mery; Haryanti, Rizki Sri; Ningsih, Ratna (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: in order to accomplish learning objectives, SOP can be developed employing learning media that can transmit messages, students attention, interest, thoughts, and feelings during learning activities. This is made possible by the development of modern technology. The SOP for laboratory equipment utilization, which is already in place and was developed in accordance with the work instructions for each piece of equipment, serves as a guide for the execution of practical work in the nursing laboratory. Through a rapid response code-connected tutorial video of the SOP, the study aims to improve students' proficiency in laboratory operations, namely in the installation of the syringe pump. (Code QR) Methods: This study uses a quasi-experimental methodology and is quantitative in nature. There are control and treatment groups in this study's design. Students in the treatment group used a video tutorial SOP via a quick response code link, while the control group received a written SOP on how to install the Aitecs/Sep 10S Plus syringe pump, which is frequently used in the laboratory of the D.III Nursing Study Program in Palembang. After that, a questionnaire was used to collect data. Total sampling was the method employed, and 93 third-year students were included. Results: The average proficiency of students in the control and intervention groups during the syringe pump installation process differed before and after they were given a video and standard operating procedure. Conclusion: There is a difference in the average skills of lab syringe pump installation between the intervention group and the control group. Keywords, QR code, SOP syringe pump, Vidio. ABSTRAK Latar Belakang : Dengan kemajuan teknologi modern, SOP dapat dibuat dengan menggunakan media pembelajaran yang bisa menyalurkan pesan, perhatian, minat, pikiran dan perasaan mahasiswa dalam kegiatan pembelajaran untuk mencapai tujuan pembelajaran. Pelaksanaan praktikum di Laboratorium Keperawatan berpedoman pada SOP penggunaan alat laboratorium, SOP tersebut sudah ada dan dibuat sesuai dengan instruksi kerja masing-masing alat. Tujuan penelitian ini adalah untuk meningkatkan kemampuan mahasiswa dalam kegiatan keterampilan skill laboratorium khususnya pemasangan alat syringe pump melalui vidio tutorial SOP dalam link quick response code (QR code). Metode : Penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian quasi eksperimen. Desain penelitian ini melibatkan kelompok kontrol dan perlakuan. Kelompok kontrol adalah mahasiswa yang diberikan SOP tertulis tentang pemasangan syringe pump Aitecs/Sep 10S Plus yang biasa digunakan di Laboratorium Program Studi D.III Keperawatan Palembang, sedangkan kelompok perlakuan adalah mahasiswa yang menggunakan media video tutorial SOP dalam link quick response code (QR code). Kemudian pengumpulan data dilakukan dengan cara menggunakan kuisioner. Teknik pengambilan sampel yang digunakan adalah total sampling yaitu sebanyak 93 orang mahasiswa tingkat III.. Hasil : terdapatnya perbedaan rata-rata keterampilan mahasiswa saat melakukan pemasangan syringe pump pada kelompok kontrol dan intervensi sebelum dan sesudah diberikan video dan SOP pemasangan syiringe pump. Kesimpulan : Terdapatnya perbedaan rata-rata keterampilan skill lab pemasangan syringe pump pada kelompok intervensi dan kelompok kontrol. Kata kunci : QR code, SOP syringe pump, Vidio.